(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Improving student achievement is vital for our nation’scompetitiveness. Scientific research shows how the physical classroomenvironment influences student achievement. We outline policy implications ofthe scientific findings—noting relevant policy audiences—and specify criticalfeatures of classroom design that can improve student achievement, especiallyfor the most vulnerable students. Recentevidence about the effects of class size on academic achievement fromrandomized experiments points to positive effects of small classes. However,the evidence about the mechanism producing these effects is less clear. Somescholars have argued for mechanisms that would imply greater effects of smallclasses for low-achieving students. We studied how specific motivational processes arerelated to the salience of mastery and performance goals in actual classroomsettings. Students who perceived an emphasis on mastery goals in the classroomreported using more effective strategies, preferred challenging tasks, had amore positive attitude toward the class, and had a stronger belief that successfollows from one’s effort. Students who perceived performance goals as salienttended to focus on their ability, evaluating their ability negatively andattributing failure to lack of ability.